2019
DOI: 10.1021/acs.langmuir.9b00699
|View full text |Cite|
|
Sign up to set email alerts
|

Interfacial Rheology of Charged Anisotropic Cellulose Nanocrystals at the Air–Water Interface

Abstract: Cellulose nanocrystals (CNCs) have received attention as a biological alternative for the stabilization of fluid interfaces, yielding biocompatible and sustainable emulsions, foams, and aerogels. The interfacial behavior of nanoparticles with shape anisotropy and surface charge like CNCs is still poorly understood, although it ultimately dictates the mechanical properties and stability of the macroscopic colloidal material. Here, we report on the linear and nonlinear interfacial dilatational and shear rheology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…In this work, we have therefore explored the idea to use the same flow-focusing method by Mittal et al 37 as a generalized mixing experiment to study the time-resolved gel transition of CNC dispersions, triggered by the shielding effect of counter monovalent ions (Na + ) using the scanning-SAXS technique. Even though there have been studies to describe the nanosized structures of CNFs and CNCs at various electrostatic conditions using SAXS, [40][41][42][43] resolving the kinetics of these transitions in real time provides a deeper insight into the nanoscale interactions leading to optimized material processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have therefore explored the idea to use the same flow-focusing method by Mittal et al 37 as a generalized mixing experiment to study the time-resolved gel transition of CNC dispersions, triggered by the shielding effect of counter monovalent ions (Na + ) using the scanning-SAXS technique. Even though there have been studies to describe the nanosized structures of CNFs and CNCs at various electrostatic conditions using SAXS, [40][41][42][43] resolving the kinetics of these transitions in real time provides a deeper insight into the nanoscale interactions leading to optimized material processes.…”
Section: Introductionmentioning
confidence: 99%
“…12 Their surface charge allows the modulation of CNC interactions from repulsive to attractive by targeted salt addition, making CNCs an interesting model system to investigate the effect of particle interactions on adsorbed nanoparticle layers. 13,14 CNC-stabilized emulsions reveal extraordinary stability against environmental inuences like heat, pH, ionic strength, and even gastric conditions. [15][16][17][18] Despite successful application in O/W emulsions, the adsorption and interactions of CNCs for different oils are mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Biological and biocompatible alternatives for interface stabilization have also gained attention recently and their impact on interfacial rheology is of interest [229,230]. Bertsch an co-workers [231] studied cellulose nanocrystals (CNC) at the air/water interface and showed that the interaction between these anisotropic particles at the interface is a major factor on the viscoelastic response of the layer. Their results illustrated that at a low surface coverage and low ionic strength, which yield a repulsive interparticle interaction, E is negligible.…”
Section: Homogeneous Particlesmentioning
confidence: 99%